Anaphora and Deixis in Tiberian Hebrew: Semantically Mapping the Case for a Distance-Neutral Demonstrative - Kummerow, David (HIPHIL Novum, 2014)
This article focusses on the issue of deixis and anaphora in Tiberian Hebrew, with the particular aim of ascertaining the functions of the demonstrative paradigm of זֶה and theparadigm of the independent third-person pronoun, הוּא which is often also said to have a remote demonstrative function. Using typological works on demonstratives, a semantic map for demonstrative–anaphoric functions is proposed, which helps to concretely represent the functions of the two paradigms. The finding is that in terms of deictic function, the זֶה paradigm is unmarked for distance, being used for both distal and near referents. In contrast, the הוּא paradigm does not have a deictic function, but is primarily used for various anaphoric functions, as well as having a recognitional function.